IMPACT OF INTERNET ON THE MENTAL HEALTH OF YOUNG ADULTS IN VISAKHAPATNAM - PENTAKOTA, VASUNDHARA; DUSI, RATNA HARIKA; GARDAS, VASUNDARA; SALOMI, SUMERA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The extreme and constant use of internet use has been reported to be associated with depression and other adverse physical health conditions. The purpose of this research is to investigate the relationship between the frequency of internet usage among the university students of Visakhapatnam, India, and their health problems and depression levels. Methods: The study sample consists of 100 university students studying at a university in Visakhapatnam, India. Distribution of the sample by gender was 43 males and 50 females. Questionnaires were administered to students in groups, in a class environment, by the author. Participation was voluntary. In total, 100 students participated in this study. Seven of them had to be excluded for not responding properly to all questionnaires, so the final sample consisted of 93 participants. Results: The results indicate a significant association between depression and the intense internet usage (>5–7 h/daily), with Chi-square value 23.80 and p<0.01. Furthermore, as the internet usage increases, there is a significant rise in systolic blood pressure with F=3.74 and p<0.05. Conclusion: This study indicates that intense internet usage is definitely leading to mental health problems like depression and also other physical health issues like increased blood pressure.